Mapping of mangrove forest and carbon stock estimation of east coast Surabaya, Indonesia - ZAINUL HIDAYAH; HERLAMBANG AULIA RACHMAN; ABD. RAHMAN AS-SYAKUR (Society for Indonesian Biodiversity, 2022)
Abstract. Hidayah Z, Rachman HA, As-Syakur AR. 2022. Mapping of mangrove forest and carbon stock estimation of east coast Surabaya, Indonesia. Biodiversitas 23: 4826-4837. The mangrove forests on Surabaya's east coast are an important protected area, providing habitat for a variety of marine organisms and water birds. This area is also vital for carbon storage and sequestration. The purpose of this research is to determine the changes in mangrove areas over the last 20 years and to calculate the amount of carbon stored in these mangrove forests. Changes in the area of mangrove forests and Normalized Difference Vegetation Indices (NDVI) were determined using Landsat-7 in 2000 and Landsat-8 in 2020. The vegetative carbon stock of mangrove stands was calculated using allometric measurements. The study results reveal that the mangrove forest area has increased significantly from 257.13 ha in 2000 to 753.48 ha in 2020. The results of regression models also show that NDVI has a significant influence on aboveground biomass (AGB), as indicated by the coefficient of determination (R2) = 0.7 (F test, df = 28, p-value < 0.05). The estimated aboveground and belowground carbon stock is 46.35 ± 13.65 ton C ha-1 and 13.65 ± 6.74 ton C ha-1 respectively. Accordingly, it is observed that the mangrove forest of East Coast Surabaya can sequester at least a total of 192.72 tons CO2 ha-1 in above and belowground biomass.